The creativity of the resistance after the 2020 Belarusian presidential election - Codogni, Paulina (Creativity Studies, 2025)
The protests that followed the 2020 Belarusian presidential election marked an unprecedented display of creativity as a tool of resistance. This study introduces the theoretical model of creative resistance as a civic awakening, demonstrating how creativity in 2020–2021 Belarusian protests operate on two levels: as 1) symbolic resistance to oppressive regimes and as 2) a mechanism for cultural renewal. In the Belarusian case, acts such as the reclamation of historical symbols, the leadership of women, and the innovative use of art and humour went beyond political defiance. They catalyzed a process of cultural rebirth, reasserting suppressed national identity and collective memory. This model offers a framework to analyze how creativity in social movements can challenge authoritarianism while reshaping national identities. The study provides insights relevant to broader discussions of political resistance, highlighting the dual role of creativity as both a tool for opposition and a vehicle for cultural regeneration.